Community-Based Ecotourism: A Case Study of Pentingsari Village - Riswandha Risang Aji; Visilya Faniza (Departement of Architecture, Universitas Islam Indonesia, 2024)
Environment is related to tourism as one of its components to maintain tourism sustainability. Eco-tourism is environment-based tourism that run by community to improve community capital which lived in its community. The community capitals that can be an input to community-based tourism which will practice the eco-tourism. This research aimed to explain how the eco-tourism could be implemented through community-based tourism. The findings of this research were Pentingsari tourism village reached self-organization through community-based tourism concept by using human and social capitals that the community have, Pentingsari tourism village reached self-sustainability through community-based tourism concept by using natural and cultural capitals, and from self-organization and self-sustainability Pentingsari tourism village could provide eco-tourism to its tourists. This research concluded eco-tourism in Pentingsari village could be reached by using self-organization and self-sustainability. Self-organization and self-sustainability could be reached by using community capitals in community-based tourism concept to develop the tourism in Pentingsari. Keywords: capital; community; ecotourism; sustainable; village